2006
DOI: 10.1111/j.1365-2184.2006.00404.x
|View full text |Cite
|
Sign up to set email alerts
|

High‐potentiality preliminary selection criteria and transformation time‐dependent factors analysis for establishing Epstein–Barr virus transformed human lymphoblastoid cell lines

Abstract: Infection of freshly isolated and cryopreserved lymphocytes with Epstein-Barr virus (EBV) leads to the establishment of human B lymphoblastoid cell lines (LCLs). Techniques for optimal infection of the lymphocytes are vital for the establishment of a human biobank. The present study found that more than half (58-86%) of such established LCLs had transport times of less than 48 h, cell densities exceeding 10(6) cells/ml and cell viabilities greater than 90%. After EBV infection, 3306 freshly isolated lymphocyte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 18 publications
1
11
0
Order By: Relevance
“…Following 3 weeks, the frequency of transformation was evaluated based on the number of wells containing growing transformed B cells. Using the standard EBV transformation protocol in normal peripheral PBMCs, we and others (Chang et al 2006) have already shown that transformed B cells are established within 3-5 weeks after EBV infection. In the present study we employed an improved transformation protocol using irradiated fetal fibroblast feeder cells and tenfold concentrated EBV stock which accelerates the transformation process (data not presented).…”
Section: Ebv Transformation and Limiting Dilution Of B Cells Infectedmentioning
confidence: 85%
“…Following 3 weeks, the frequency of transformation was evaluated based on the number of wells containing growing transformed B cells. Using the standard EBV transformation protocol in normal peripheral PBMCs, we and others (Chang et al 2006) have already shown that transformed B cells are established within 3-5 weeks after EBV infection. In the present study we employed an improved transformation protocol using irradiated fetal fibroblast feeder cells and tenfold concentrated EBV stock which accelerates the transformation process (data not presented).…”
Section: Ebv Transformation and Limiting Dilution Of B Cells Infectedmentioning
confidence: 85%
“…12 Frozen viable PBMCs are fit-for-purpose, not only for immunomagnetic sorting of purified monocyte and lymphocyte populations, following cryopreservation, 13 but also for functional studies, 14 immunophenotyping, 15 establishment of lymphoblastoid cell lines (LCL) by Epstein Barr virus (EBV) transformation, 16 and purification of CD34 + cells. 17 The surrogate QC assay for either EBV transformation success 18 or immunophenotyping and proliferation assays 14 has shown cell viability, with a qualification cut-off at around 70% viability. Therefore, implementation of a PT scheme on cell viability for repositories, which process and cryopreserve mononuclear cells for all the above-mentioned end-uses, is of critical importance.…”
Section: S Hipment Of Viable Cells Between Research Laboratoriesmentioning
confidence: 99%
“…The HV suspension corresponded to the Jurkat cells incubated according to manufacturer's instructions (cell passage [1][2][3][4][5][6][7][8] or freshly isolated cells from whole blood for PBMCs; the IV suspension was obtained, following incubation of HV suspension of Jurkat cells (cell passage 1-8) or fresh isolated PBMCs for one week at + 4°C; the LV suspension was obtained, following incubation of Jurkat cells (cell passage [10][11][12][13][14][15][16][17][18] for one week at + 4°C.…”
Section: Samples Usedmentioning
confidence: 99%
“…Epstein-Barr virus transformation was performed based on our previous study (6). Briefly, the cell pellet containing lymphocytes (cell number is in the range of 10 6 -10 7 cells) was infected with 1 mL EBV at 37 ° C for 1 h. Then, the sample was centrifuged at 270 g for 10 min to remove the EBV.…”
Section: Epstein-barr Virus Transformationmentioning
confidence: 99%
“…It has well accepted that growth of LCLs could be enhanced by mitogen such as PHA (4,11,12) and utilization of PHA in EBV transformation has been as standard EBV transformation protocol (12). Dosages of PHA that had been employed in EBV transformation were varied (10% PHA in Beck et al (4); 1% PHA in Chang et al (6)). In purpose of material saving, EBV transformation in this experiment was performed in the presence or absence of 1% PHA.…”
Section: Effects Of Pha On Growth Of Ebv-infected B Lymphocytes In Dementioning
confidence: 99%